2021
DOI: 10.1155/2021/5551036
|View full text |Cite
|
Sign up to set email alerts
|

Pan‐Cancer Analysis of the Prognostic and Immunological Role of HSF1: A Potential Target for Survival and Immunotherapy

Abstract: Emerging evidence revealed the significant roles of heat shock factor 1 (HSF1) in cancer initiation, development, and progression, but there is no pan-cancer analysis of HSF1. The present study first comprehensively investigated the expression profiles and prognostic significance of HSF1 and the relationship of HSF1 with clinicopathological parameters and immune cell infiltration using bioinformatic techniques. HSF1 is significantly upregulated in various common cancers, and it is associated with prognosis. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 52 publications
1
71
0
Order By: Relevance
“…Notably, our GSEA and KEGG results suggested that HSF2 was also involved in many immunity-associated pathways (IL−17 signaling pathway and the adaptive immune system) and various microbial infections (hepatitis B, shigellosis, Yersinia infection, and herpes simplex virus 1 infection) (Figures 5,6). A recently study showed that HSF2 was upregulated in ulcerative colitis and was negatively associated with colon inflammation in mice (Wang W. et al, 2020;Zhang F. et al, 2021). NLRP3 inflammasome activation and IL-1β secretion are greatly enhanced in HSF2−/− DSS model mice (Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, our GSEA and KEGG results suggested that HSF2 was also involved in many immunity-associated pathways (IL−17 signaling pathway and the adaptive immune system) and various microbial infections (hepatitis B, shigellosis, Yersinia infection, and herpes simplex virus 1 infection) (Figures 5,6). A recently study showed that HSF2 was upregulated in ulcerative colitis and was negatively associated with colon inflammation in mice (Wang W. et al, 2020;Zhang F. et al, 2021). NLRP3 inflammasome activation and IL-1β secretion are greatly enhanced in HSF2−/− DSS model mice (Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, serum HSF2 levels are positively correlated with the expression of IL-1β and TNF-α. Knockdown of HSF2 potentiates the production of IL-1β and TNF-α induced by LPS (Miao et al, 2014;Wang W. et al, 2020;Zhang et al, 2020;Santopolo et al, 2021;Zhang F. et al, 2021). Here, to further estimate the relationships between HSF2 and the TME, we first examined the correlation of HSF2 expression and the abundance of different infiltrating immune cells across different cancer types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GSEA was used to investigate the potential mechanisms of hepcidin. The GO, KEGG and GSEA results were explored using the R package ClusterProfiler ( Chen et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Gene Ontology, Kyoto Encyclopedia of Genes and Genomes and Gene Set Enrichment Analysis GO analysis, KEGG analysis and GSEA were applied to investigate the biological functions and potential mechanisms of HSF2 in HCC. GO analysis is a powerful bioinformatics method that annotates and categorizes genes according to biological processes (BPs), cellular components (CCs) and molecular functions (MFs) (Chen et al, 2021). GSEA was used to investigate the potential mechanisms of hepcidin.…”
Section: Immunohistochemistry Analysismentioning
confidence: 99%